Healthcare resource utilization and costs associated with venous thromboembolism in cancer patients treated with anticoagulants. (2nd November 2019) - Streiff, Michael; Milentijevic, Dejan; McCrae, Keith R.; Laliberté, François; Lejeune, Dominique; Lefebvre, Patrick; Schein, Jeff; Khorana, Alok A.
Abstract: Objective: The standard of care for cancer-related venous thromboembolism (VTE) has been low molecular weight heparin (LMWH), but oral anticoagulants are also widely prescribed. This study compared VTE-related healthcare resource utilization and costs of cancer patients treated with anticoagulants. Methods: Claims data from Humana Database (January 1, 2013–May 31, 2015) were analyzed. Based on the first anticoagulant received, patients were classified into LMWH, warfarin, or rivaroxaban cohorts. Characteristics were evaluated during the 6 months pre-index date (i.e. the first VTE); VTE-related resource utilization and costs were evaluated during follow-up. Cohorts were compared using rate ratios, and p -values and 95% confidence intervals were calculated. Healthcare costs were evaluated per-patient-per-year (PPPY) and compared using mean cost differences. Results: A total of 2, 428 patients (LMWH: n = 660; warfarin: n = 1, 061; rivaroxaban: n = 707) were included. Compared to patients treated with LMWH, patients treated with rivaroxaban had significantly fewer VTE-related hospitalizations, hospitalization days, and emergency room and outpatient visits, resulting in an increase of 12, 000 VTE-related healthcare costs PPPY with LMWH vs rivaroxaban. Patients treated with rivaroxaban had significantly lower VTE-related resource utilization compared to patients treated with warfarin; however, VTE-related costs were similar between cohorts. The higher drug costs (1, 519) were offset by significantly lower outpatient (−1, 039) and hospitalization costs (−522) in rivaroxaban relative to the warfarin cohort. Conclusions: Healthcare resource use and costs associated with VTE treatment in cancer patients are highest with LMWH relative to warfarin and rivaroxaban.